Deficient Emotional Self-Regulation and Sleep Problems in ADHD with and without Pharmacological Treatment - Sanabra, Miriam; Gómez-Hinojosa, Tary; Grau, Núria; Alda, Jose A. (Journal of attention disorders, 2022)
Objective: The purpose of this study is to analyse DESR and its influence on sleep parameters in three different groups of children and adolescents: a group newly diagnosed with ADHD naïve, a group with ADHD under pharmacological treatment and a control group. Method: Subjects were a total of 327 children and adolescents. Two groups diagnosed with ADHD: 108 medication-naïve and 80 under pharmacological treatment; and one group with 136 healthy subjects. DESR was defined using anxious/depressed, attention problems and aggressive behaviors (AAA) scales from the Child Behavior Checklist (CBCL), and sleep through the Sleep Disturbance Scale for Children. Results: Significant differences were found comparing the three groups (p = .001), with a significantly higher profile on DESR in ADHD subjects, especially those who did not undergo treatment, and a positive correlation between DESR and sleep. Conclusion: Children and adolescents with ADHD without treatment present higher DESR than healthy controls and consequently higher sleep problems.